EVALUASI PELAKSANAAN PENDIDIKAN KARAKTER (Studi Kasus di Sekolah Dasar Ma’arif Ponorogo) - SYAIKHUDIN, AHMAD (Universitas Islam Negeri Raden Intan Lampung, 2014)
Many educational institutions state that the learning process occured in the school is based on character education. However, in practice, the process did not fully meet the goal of character education. Although the learning in educational institutions has already planned several educational instrument character, but it is only as a topic of the discussion, it has not been implemented yet or the implementation has not been on the expected education character. Elementary School Ponorogo Maarif is one of the schools that implement character education in the learning process in the last two years. The school is able to implement character education in the learning process because the students, the teachers, and the school supported the implementation. This paper aims at finding out the implementation of the nation's culture and character education in elementary schools Ma’arif Ponorogo.